2017
DOI: 10.1093/nar/gkx1127
|View full text |Cite
|
Sign up to set email alerts
|

NS3 helicase from dengue virus specifically recognizes viral RNA sequence to ensure optimal replication

Abstract: The protein–RNA interactions within the flavivirus replication complex (RC) are not fully understood. Our structure of dengue virus NS3 adenosine triphosphatase (ATPase)/helicase bound to the conserved 5′ genomic RNA 5′-AGUUGUUAGUCU-3′ reveals that D290 and R538 make specific interactions with G2 and G5 bases respectively. We show that single-stranded 12-mer RNA stimulates ATPase activity of NS3, however the presence of G2 and G5 leads to significantly higher activation. D290 is adjacent to the DEXH motif foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 71 publications
4
52
0
Order By: Relevance
“…Furthermore, it has been shown that some single-amino-acid mutation in R538, R225 and R268 of DENV, which affect the replication of DENV (17, 58). Another study report that the Asp-285-to-Ala substitution of the JEV NS3 protein abolished the ATPase and RNA helicase activities (63).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that some single-amino-acid mutation in R538, R225 and R268 of DENV, which affect the replication of DENV (17, 58). Another study report that the Asp-285-to-Ala substitution of the JEV NS3 protein abolished the ATPase and RNA helicase activities (63).…”
Section: Discussionmentioning
confidence: 99%
“…All remaining top conserved NS3 epitopes were found to lie within the conserved flavivirus motifs and map to the helicase domain [57]. Remarkably, while these NS3 epitopes were located far from each other in the primary structure ( Fig 4B), they localized in the tertiary structure around the groove that is important for interacting with viral RNA and facilitating its unwinding [50,58].…”
Section: (S5 Fig)mentioning
confidence: 97%
“…Most of the residues within these epitopes are located in regions that provide stability to the polymerase complex [52]. (B) (Left panel) Coverage of the top conserved NS3 epitopes (Fig 3) along the protein sequence, and (right panel) their locations in the corresponding tertiary structure (PDB ID 5XC6) [50]. Although these epitopes are spread out in the primary structure, they localize near the RNA binding groove of the helicase domain [58].…”
Section: Identifying Epitopes That Can Serve As Targets For a Universmentioning
confidence: 99%
“…Interestingly, trans complementation with the NS3 mutants S138A or R461Q in which the protease and the helicase are inactive, respectively, rescued virus production, suggesting that the function of NS3 during virus assembly is independent from its known enzymatic activity. Lastly, structural studies suggest that binding of NS3 to specific 5′ UTR sequences could function as a molecular signature to guide newly synthesized vRNA out of the replication complex [99]. Nevertheless, biophysical and biochemical evidence to support this hypothesis is lacking.…”
Section: Post-replicative Functions Of Ns Proteinsmentioning
confidence: 99%